PENGARUH KOMPETENSI, KOMPENSASI, DAN TEKANAN KERJA TERHADAP KINERJA PNS DI BKPSDM KABUPATEN NGANJUK - Ardiansyah, Roiz; Subagyo; Widodo, Moch. Wahyu (Universitas Nusantara PGRI Kediri, 2024)
The performance of civil servants (PNS) is a crucial factor in the success of government, contributing to improving the quality of public services and achieving national development goals. The three main factors that influence civil servant performance are competence, compensation, and work pressure. Competence includes the civil servant's ability to carry out tasks effectively, compensation is a reward for performance, and work pressure refers to conditions that can cause physical and psychological imbalance. This research aims to analyze the influence of these three factors on the performance of civil servants at the Nganjuk Regency Personnel and Human Resources Development Agency (BKPSDM), using a quantitative approach and correlational techniques. With a research population and sample of 30 civil servants, the results show that competence, compensation and work pressure have a positive and significant influence on the performance of civil servants in this agency.